The occupation of Iraq winning the war, losing the peace - Allawi, Ali A., 1947- (Yale University Press, 2007)
What really led the United States to invade Iraq, and why did the events failed to unfold as planned? This book examines what the US did and didn't know at the time of the invasion, the reasons for the confused and contradictory policies that were enacted, and the emergence of the Iraqi political class during the difficult transition process.